Making HPV vaccines efficient: Cost-effectiveness analysis and the economic assemblage of healthcare in Colombia (2018)
Cost-eff ectiveness analysis is a strategy of calculation whose main objective is to compare for making decisions about the best, the most effi cient solution (costs vs benefi ts) to a particular problem. Cost-eff ectiveness analysis not only provides a framework to compare healthcare interventions which in practice seem incommensurable; it also performs a set of assumptions regarding the nature of healthcare and individuals’ behaviour. This article analyses the role of cost-eff ectiveness analysis as a device to produce value in the introduction of human papillomavirus vaccines to Colombia. In diff erent institutional pathways and decision-making scenarios cost-eff ectiveness has been the key issue that justifi ed the inclusions and exclusions that such technology entails. Cost-eff ectiveness justifi ed the defi nition of girls as the population target and the exclusion of boys from the risks and benefi ts of this technology. Cost-eff ectiveness analysis has been a key instrument in the sexualising and desexualising of cervical cancer and human papillomavirus vaccines through the rationalisation of economic benefi ts.